Julian of Norwich's Showings : from vision to book - Baker, Denise Nowakowski, 1946- (Princeton legacy library., 1994)
The first woman known to have written in English, the fourteenth-century mystic Julian of Norwich has inspired generations of Christians with her reflections on the ""motherhood"" of Jesus, and her assurance that, despite evil, ""all shall be well."" In this book, Denise Baker reconsiders Julian not only as an eloquent and profound visionary but also as an evolving, sophisticated theologian of great originality. Focusing on Julian's Book of Showings, in which the author records a series of revelations she received during a critical illness in May 1373, Baker provides the first histor